2022
DOI: 10.1002/aoc.6871
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzo[4,5]imidazo[1,2‐a]indolo[1,2‐c]quinazolines from 2‐(2‐bromoaryl)indoles and 2‐methoxybenzimidazoles under recyclable magnetic MOF‐199 catalysis

Abstract: 2‐(2‐Bromoaryl)indoles react with 2‐methoxybenzimidazoles in DMF in the presence of a catalytic amount of recyclable Fe3O4@SiO2@MOF‐199 along with K2CO3 to afford a series of benzo[4,5]imidazo[1,2‐a]indolo[1,2‐c]quinazolines in good yields. The reaction applies to a broad scope of 2‐(2‐bromoaryl)indoles containing electron‐donating or ‐withdrawing substituents on bromophenyl and indole moieties, and alkyl substituents at 3‐position of indole moiety. A reaction pathway involving a copper‐catalyzed Ullmann‐type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…One-pot regioselective synthesis of benz [4,5]imidazo[1,2-a]quinazoline was reported by Fang, S. et al Anilinobenzimidazole (25) showed a reaction with various aromatic aldehydes bearing halogen groups and a nitro group (57a-o) in DMF to afford the targeted products (58a-j) in 59-97% yields [73]. Transition metal-free coupling reaction to form benzimidazoquinazoline was carried out by Kim et al under recyclable magnetic MOF-199 catalysis [74].…”
Section: Transition Metal-free Tandem Processmentioning
confidence: 99%
“…One-pot regioselective synthesis of benz [4,5]imidazo[1,2-a]quinazoline was reported by Fang, S. et al Anilinobenzimidazole (25) showed a reaction with various aromatic aldehydes bearing halogen groups and a nitro group (57a-o) in DMF to afford the targeted products (58a-j) in 59-97% yields [73]. Transition metal-free coupling reaction to form benzimidazoquinazoline was carried out by Kim et al under recyclable magnetic MOF-199 catalysis [74].…”
Section: Transition Metal-free Tandem Processmentioning
confidence: 99%